2018
DOI: 10.1002/rmv.1980
|View full text |Cite
|
Sign up to set email alerts
|

Management of adenovirus infection in patients after haematopoietic stem cell transplantation: State‐of‐the‐art and real‐life current approach

Abstract: The important insights gained over the past years in diagnosis and treatment of invasive adenoviral infections provide new paradigms for the monitoring and clinical management of these life-threatening complications. A meeting was held to discuss and subsequently disseminate the current advances in our understanding of the aetiology/pathogenesis and future treatment options facilitating effective control or prevention of adenovirus-related diseases in the allogeneic haematopoietic stem cell transplant setting.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
74
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 79 publications
(75 citation statements)
references
References 56 publications
1
74
0
Order By: Relevance
“…For cytolytic viral infections such as AdV, plasma viremia may provide a quantitative measure of tissue damage in the most commonly affected organs: the gastrointestinal tract, lungs, liver, or kidneys [17]. In our study, over half the pediatric allo-HCT recipients who developed AdV viremia surpassed the level of ≥1000 copies/ml, an accepted threshold for the initiation of preemptive treatment [7,18]. Analyses of AdV viral load in these patients revealed a strong association with risk of mortality.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…For cytolytic viral infections such as AdV, plasma viremia may provide a quantitative measure of tissue damage in the most commonly affected organs: the gastrointestinal tract, lungs, liver, or kidneys [17]. In our study, over half the pediatric allo-HCT recipients who developed AdV viremia surpassed the level of ≥1000 copies/ml, an accepted threshold for the initiation of preemptive treatment [7,18]. Analyses of AdV viral load in these patients revealed a strong association with risk of mortality.…”
Section: Discussionmentioning
confidence: 75%
“…Pediatric allogeneic hematopoietic stem cell transplant (allo-HCT) recipients with nonmatched sibling sources are at high risk of developing adenovirus (AdV) infections, particularly during the immediate posttransplant period before immune reconstitution has occurred [1][2][3][4][5][6][7]. AdV viremia is widely considered to be an indicator of disease dissemination [6,8,9], with higher levels of AdV viremia (≥1000 copies/ml) shown to be associated with mortality in single-center studies [7,10]. Guidelines have thus recommended antiviral treatment in high-risk patients with AdV viremia [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In allogeneic HCT, HAdV replication is more frequently detected, which is, however, mostly due to the widespread screening of blood and gastrointestinal specimens from a-or presymptomatic patients considered to be at highest risk, such as children and those receiving alemtuzumab therapies (203). Conversely, HAdV is less frequently reported in respiratory specimens from allogeneic HCT patients with RTID (204,205).…”
Section: Other Carvs In Sot and Allogeneic Hctmentioning
confidence: 99%
“…Conversely, HAdV is less frequently reported in respiratory specimens from allogeneic HCT patients with RTID (204,205). Accordingly, the levels and dynamics of HAdV in different anatomic sites is not well understood, with the exception of blood and stool samples, and no generalized thresholds using international calibrators have been established (203,206,207). A large retrospective study of 687 allogeneic HCT patients identified HAdV in 64 (9.3%) cases presenting mostly as gastrointestinal disease or hemorrhagic cystitis but in 3 (0.5%) cases as HAdV pneumonitis, which eventually had a lethal outcome (204).…”
Section: Other Carvs In Sot and Allogeneic Hctmentioning
confidence: 99%